(untitled) (Revista Latino-Americana de Enfermagem, 2010)
This study aimed to evaluate the quality of life of female gynecological cancer patients submitted to antineoplastic chemotherapy Between August 2007 and April 2009, 50 patients who were undergoing chemotherapy at an outpatient chemotherapy unit in Uberaba - MG were interviewed, by applying the instrument of evaluation of Quality of Life of the World Health Organization, WHOQOL-BREF. The results showed that the domain most affected was the Physical and the more preserved, the Social, with the mean of the general quality of life above the means obtained in other studies. All domains correlated significantly with the general quality of life. It was evident then that the quality of life of these women is satisfactory, however it is suggested that the domains with lower scores be the targets of more accurate observations during multi-professional interventions in order to provide a better quality of life during the chemotherapy treatment.